Compromises in Healthcare Privacy due to Data Breaches - Srinivasan, S. (European Scientific Journal, ESJ, 2016)
Healthcare privacy is essential for people because any leaked information could be used against the interests of the person in providing healthcare. This is especially true in countries where the individual is responsible for getting the health insurance. In places where the healthcare coverage is included as national policy, such leaked information could be used to deny care. Healthcare industry is highly data intensive and people would need healthcare coverage in places beyond their home base. Making healthcare data available to service providers facilitates rendering quality care. This necessitates centralized storage of such data for easy access. Hackers are motivated to seek out centralized data stores due to the volume of data that they could get. Leaked data could be used by unscrupulous individuals to offer treatments that might help the people. Since such individuals are desperate to get treatment they fall victim to such scams. In this paper we first analyze some of the major data breaches in healthcare globally. We include at least one country from all the continents to see how the policies and protections for health data differs. Then we present technology-based solutions to prevent such breaches. We conclude the paper with several policy guidelines to show how the holders of health data could provide adequate data protection to prevent data breaches. This has become all the more essential because the most often breached sites are in healthcare and stolen data are used to pry on unsuspecting and vulnerable people.